2020
DOI: 10.1021/acs.jmedchem.9b01379
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Validation of a Harmine-Based, Central Nervous System (CNS)-Avoidant, Selective, Human β-Cell Regenerative Dual-Specificity Tyrosine Phosphorylation-Regulated Kinase A (DYRK1A) Inhibitor

Abstract: Recently, our group identified that harmine is able to induce β-cell proliferation both in vitro and in vivo, mediated via the DYRK1A-NFAT pathway. Since, harmine suffers from a lack of selectivity, both against other kinases and CNS off-targets, we therefore sought to expand structure−activity relationships for harmine's DYRK1A activity, to enhance selectivity for off-targets while retaining human β-cell proliferation activity. We carried out optimization of the 9-N-position of harmine to synthesize 29 harmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 85 publications
0
62
1
Order By: Relevance
“…Chemicals. Harmine-HCl was synthesized in the Drug Discovery Institute at Mount Sinai (15,16). Exendin-4 was purchased from MedChemExpress (Monmouth Junction, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Chemicals. Harmine-HCl was synthesized in the Drug Discovery Institute at Mount Sinai (15,16). Exendin-4 was purchased from MedChemExpress (Monmouth Junction, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, other analogs with longer carbon lengths did not provide any improvement for DYRK1A inhibition, a result that did not align with our original docking hypothesis, which indicated that extension into solvent would be possible. Subsequent docking studies of these novel 7-C harmine analogs based on the crystal structure of DYRK1A bound to harmine analog 2-2c [39] were performed and suggested that the loss of activity with longer substituents at the 7-position could be due to interplay of several factors that diminish interactions with the DYRK1A back bone H-bond at Leu 241. These include steric hindrance, the entropic effects of longer, more flexible side chains, combined with the possibility of partially compensating additional new contacts ( Figure 3A, subpanel A-F).…”
Section: Structure-activity Relationships Of 7-substituted Harmine Anmentioning
confidence: 99%
“…After assessing the effect of these modifications on DYRK1A inhibition, we next explored the structure-activity relationships for in vitro β-cell proliferation activity of the most potent 7-O-substituted DYRK1A inhibitor harmine analogs. Compounds 1-2b and 1-3b, with DYRK1A inhibitory activities (IC 50 ) of 89 and 91 nM, respectively, were studied as previously reported [5,39,[43][44][45], for their ability to induce human β-cell proliferation in vitro as assessed by Ki-67-insulin co-immunolabeling after 4 days, our standard assay protocol [49] ( Figure 4A). Both the harmine analogues, 1-2b and 1-3b exhibited human β-cell proliferation at 10 µM ( Figure 4A).…”
Section: Effects Of Harmine Analogs On Human β-Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations